Cultural values and other perceived benefits of organized activities: A qualitative analysis of Mexican-origin parents' perspectives in Arizona. Issue 2 (3rd April 2018) - Lin, Alex R.; Simpkins, Sandra D.; Gaskin, Erin R.; Menjívar, Cecilia
ABSTRACT: The limited understanding on why Latino parents endorse organized activities is problematic given that these beliefs can help elucidate why they overcome barriers to support their children's participation. In this study, we analyzed interviews from a diverse group of 34 Mexican-origin parents who resided in Arizona. Results of the study indicate that although organized activities were perceived as contexts that can help youth gain skills reflecting mainstream American values (e.g., school engagement, interpersonal skills), parents also thought that activities promoted positive behaviors associated with their ethnic culture based on traditional values related to respeto, familism, and religiosity . The implications of this study suggest that understanding Mexican-origin parents' perspectives can help organized activity leaders design programs that fully address the benefits that families seek from organized activities.